2002
DOI: 10.1074/jbc.m204832200
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP-dependent Transcriptional Up-regulation of Phosphodiesterase 4D5 in Human Airway Smooth Muscle Cells

Abstract: Phosphodiesterase 4D (PDE4D), part of the complex cAMP-specific PDE4 family, plays a pivotal role in the regulation of airway smooth muscle relaxation by catalyzing the hydolysis of cAMP. Its gene on chromosome 5q12 encodes 5 splice variants, which show tissue-dependent expression and regulation. The genomic arrangement of PDE4D was determined using in silico methods, and a putative promoter of one of the protein kinase A-activated, long isoforms, PDE4D5 was identified. Promoter-luciferase constructs, transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 60 publications
(41 reference statements)
7
76
0
Order By: Relevance
“…For example, a CRE (TGACGTT) in the promoter of an isoform of PDE4D (PDE4D5) was shown to be involved in the cAMP responsiveness of the PDE4D5 promoter. 60 Several other lines of evidence support the involvement of the PDE4D gene in susceptibility to neuroticism and depression. A PDE4-specific inhibitor rolipram has antidepressant effects on animals and patients with major depression.…”
Section: Discussionmentioning
confidence: 95%
“…For example, a CRE (TGACGTT) in the promoter of an isoform of PDE4D (PDE4D5) was shown to be involved in the cAMP responsiveness of the PDE4D5 promoter. 60 Several other lines of evidence support the involvement of the PDE4D gene in susceptibility to neuroticism and depression. A PDE4-specific inhibitor rolipram has antidepressant effects on animals and patients with major depression.…”
Section: Discussionmentioning
confidence: 95%
“…The stimulatory effects of β-adrenergic receptor agonists on PDE4D expression might be mediated by CREB since CRE elements have been identified in the PDE4D promoter [29]. In cells other than adipocytes it has also been shown that prolonged exposition to cAMP-increasing agents results in PDE4D up-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated, in different human blood cells, that treatment with either b 2 -AR agonists (Manning et al, 1996;Seybold et al, 1998;Ortiz et al, 2000) or with a cAMP structural analogue, 8-Bromo-cAMP, leads to an upregulation of PDE4 enzymes. More recently, new evidences for a role of cAMP on PDE4 promoters have been defined (Vicini & Conti, 1997;D'Sa et al, 2002;Le Jeune et al, 2002). Furthermore, it has been shown, in an in vivo model of rat pulmonary b 2 -AR desensitisation induced by salbutamol, that the b 2 -AR binding site density was significantly reduced, and associated with an increase in the PDE3 and PDE4 activities in lung membranes of these animals (Finney et al, 2000).…”
Section: Rouget Et Almentioning
confidence: 98%